Anisotropic corrosion behavior of Sc and Zr modified Al-Mg alloy produced by selective laser melting. (1st July 2020) - Gu, Dongdong; Zhang, Han; Dai, Donghua; Ma, Chenglong; Zhang, Hongmei; Li, Yuxin; Li, Shuhui
Highlights: Corrosion behaviors on different planes of Sc- and Zr- modified Al-Mg alloy processed by selective laser melting were systematically studied using electrochemical measurements. Microstructures including precipitations, grain size distributions and crystallographic orientations on different planes of Al-Mg-Sc-Zr alloy processed by SLM were characterized using BSE and EBSD. Inner mechanisms for the anisotropic corrosion behavior were further proposed based on the microstructure analyses. Abstract: Electrochemical measurements and microstructural analyses were conducted to investigate the corrosion behaviors on different planes of Sc and Zr modified Al-Mg alloy produced by selective laser melting (SLM). Results indicated that the XY-plane exhibited a superior corrosion resistance with a lower current density ( i corr =57.1 μA cm -2 ) compared to the XZ-plane in 3.5 wt.% NaCl solution at room temperature. The microstructural analyses suggested that the anisotropic corrosion resistances of the SLM produced Al-Mg-Sc-Zr alloy related to the quite different microstructures on different planes, which included the molten pool boundary density, Al3 (Sc, Zr) precipitation distribution, grain size distribution, and crystallographic orientation.